Dekonstruksi Dimensi Estetika Seni Tari Persembahan Dalam Masyarakat Riau: Kritik Postruk Tari Kontemporer - Febrianty, Syielvi Dwi; Satria, Edi; Hamzaini, Hamzaini; Aryadi, Mirda (Asosiasi Ide Bahasa Kepri, 2024)
This research aims to apply the application of Deconstruction to the Aesthetic Dimensions of Dance as presented to the people of Riau with a focus on criticism of contemporary dance postures. Based on the theory of Deconstruction introduced by Jacques Derrida, this research aims to deconstruct the meaning and structure of traditional dance in a contemporary context. Qualitative research methods were used through indirect observation and content analysis of dance performances in Riau. It is hoped that this research will provide a deeper understanding of how the concept of Deconstruction can be applied in studying and strengthening the aesthetic aspects of traditional Riau dance art in a modern contemporary context. The results of this research show that various symbolic meanings are revealed in gender, ecological perspectives, respect for nature, ethics and manners, through dance movements, props used, decoration and clothing, up to the design of the seven floors. All components in the Malay worship dance have a deep meaning and certain complexity. This article contributes to enriching the cultural treasures behind dance which presents contemporary Riau and the deep meaning behind it.